Estimating depth of daylight zone and PSALI for side lit office spaces using the CIE Standard General Sky - Mohammad Shahriar, Abu Nur; Mohit, Mohammad Abdul (Elsevier Ltd, 2007)
The use of daylight has energy saving implications. But to harness daylight requires detailed analysis into its penetration. The paper predicts the depth of daylight zone and Permanent Supplementary Artificial Lighting of Interiors (PSALI) in a generalized high-rise office space in Kuala Lumpur, Malaysia. Using CIE Standard General Skies, two experiements are conducted to find the probable upper and lower limits of daylight penetration throughout the year. As CIE Standard General Skies are not widely incorporated into simulation software, therefore, combination of Daylight Coefficient method and Waldram Diagrams is used for daylight calculation. The lowest daylight penetration is taken as the depth of daylight zone while the difference between the lowest and highest penetration is considered for the depth of PSALI zone.